Improving the Manufacturing of Square Flange Gasket Through Lean Practices - Rashiddy Wong, Freddawati; Ahmad, Ahsana Aqilah; Nor Azaki, Mohamad Faris Aiman (International Journal of Integrated Engineering, 2025)
This paper reports a case study on production line of square flange gasket at a small and medium-sized enterprise (SME) company. The square flange gasket, a high-demand product used as a seal between two flange faces, is currently produced below satisfactory levels due to delays, causing client dissatisfaction. This study aims to identify the root causes of waste in the production line and propose solutions to improve productivity and speed up production. The methodology used in this study is based on PDCA Cycle, starting with the ‘Plan’ approach that focuses on finding the root problems through Lean Practices such as Ishikawa, Yamazumi Chart, 5 Whys Analysis and Pareto Chart using the information gained from the Gemba visit at the company. Lean Practices revealed that the longest cycle time occurs during the quality check process due to inefficient movement between the machine room and quality check room, and the lack of quick measurement tools. ‘Do’ phase is done by developing a Go/No Go Gauge as the solution for the problems that have been identified and the ‘Check’ phase will involve the implementation of the designed gauge and monitoring the results with its function and suitability. The case study will end in the ‘Act’ phase where we make improvements based on the results during ‘Check’ phases and standardise the right practices. The proposed solution led to significant improvements: a 72.73% reduction in movement distance, a 26.29% reduction in cycle time, and a 26.47% increase in weekly production. The gauge eliminated waste like waiting time and unnecessary motion, speeding up measurements. In conclusion, this study highlights the importance of Lean practice in reducing waste and boosting overall productivity.